Freedom and dissatisfaction in the works of Agnes Heller : with and against Marx - Ward, Lucy Jane (Lexington Books, 2016)
In this book, Lucy Jane Ward argues that although contemporary scholarship tends to divide Agnes Heller's work chronologically in terms of her "Marxist" and subsequent "post-Marxist" periods, a closer reading reveals her work as a continuing engagement both with and against Marx's idea of the human being rich in need